A sustainable cementitious composite reinforced with natural fibers: An experimental and numerical study. (16th May 2023) - Abedi, Mohammadmahdi; Hassanshahi, Omid; Rashiddel, Alireza; Ashtari, Hamidreza; Seddik Meddah, Mohammed; Dias, Daniel; Arjomand, M.A.; Keong Choong, Kok
Graphical abstract: Highlights: A sustainable, eco-friendly cementitious composite reinforced with natural fibers was developed and its potential to be used in infrastructural elements was successfully demonstrated. The mechanical, microstructural and durability of this green composite were assessed using several different sorts of experiments. A non-linear finite element model was developed for a detailed investigation of the composite efficiency as substructure layers of a slab track system, in terms of mechanical performance. Abstract: Eco-friendly nature, low cost, life-cycle superiority and lightweight are the key drivers pushing today's technology towards employing natural fibers as reinforcement for cementitious-based composites. The present study provides an extensive experimental and finite element analysis aiming to develop a sustainable cementitious composite reinforced with natural fibers. Different concentrations of kenaf and coconut fibers were chemically treated and incorporated into the stabilized sand and specimens were cast and compacted using a modified compaction method. The mechanical, microstructural, and durability properties of the specimens were investigated by various types of tests. A validated 3D slab track model was also developed using a finite element method, which includes all components of the railway infrastructure to assess the performances of this composite under realistic operation scenarios. The outcomes indicated that reinforcing cementitious composite with a certain amount of kenaf fiber (1.5% wt of dry sand) can significantly improve the mechanical behavior and durability performance of the composite through microstructural enhancement. This study opens proper perspectives on the immense potential of the natural fibers in order to develop sustainable, reliable and affordable cementitious composites for different infrastructures applications related to structural layers in transportation, pavements, slope protection and stabilization, embankment, and building foundation.